The last pagans of Iraq : Ibn Waḥshiyya and his Nabatean agriculture - Hämeen-Anttila, Jaakko (Islamic history and civilization, 2006)
This is the first analysis in any language of the religious, philosophical and folkloristic content of Ibn Washiyya's (d. 931) "Nabatean Agriculture". This enigmatic book, said to have been translated by Ibn Washiyya from Syriac into Arabic, contains much material on Late Antique Paganism in Iraq and semi-learned reception of Greek philosophical thought. The first part of the present book studies the question of authenticity, authorship and context of the "Nabatean Agriculture", dated by the author to around 600 AD. The second part consists of 61 translated and annotated excerpts of the "Nabatean Agriculture", until now available only in the Arabic original, as well as introductions to the world view of the text